The Legal Framework Governing the Offence of Environmental Pollution in Jordan and the Sultanate of Oman - GHARIBEH, Ashraf Mohamad; MAKHMARI, Mohammed Rashid Ahmed Al; HAF, Radwan Ahmad Al; ELAYAT, Mohammad Njim Ibrahim; ALSHARQAWI, Ahmad Hussein (Journal of Environmental Management and Tourism, 2023)
The focus of this study pertains to the legal regulations governing environmental pollution offences, as stipulated by the Environmental Protection Law No. 6 of 2017 and its subsequent revisions. Initially, the study examined the definitions of environmental pollution in accordance with the methodology employed by Jordanian lawmakers and international conferences. Subsequently, an analysis was conducted on the Environmental Protection Law No. 6 of 2017 and its subsequent amendments. This was followed by a determination of the fundamental components upon which the criminal offence is predicated. Additionally, a review of select cases that were brought before the Jordanian judiciary was undertaken. The environmental policy in Oman legislation underscores adopting a multifaceted approach, sometimes emphasizing obligatory measures and resorting to prohibitive or unrestricted policies. It is apparent that the responsibility for safeguarding the environment from pollution is not solely vested in the state but is a collective responsibility shared among individuals and society as a whole, as reinforced by the provisions of Article 6. This underscores the importance of environmental protection as an effective means to combat wrongdoing, thus the enactment of Law No. 26 for Environmental Protection and Pollution Control, which establishes specific legal principles to define criminal behaviour and prescribes penalties, adhering to the fundamental legal principle that "there is no crime and no punishment except by law."